Usefulness of prostate specific antigen density in detecting prostate carcinoma: A hospital-based study in patients with prostate biopsies (Journal of Pathology of Nepal, 2022)
Background: Prostate-specific antigen density has been suggested to enhance the diagnostic efficacy of serum prostate-specific antigen alone in detecting prostate cancer, thereby reducing unnecessary biopsies and associated morbidities. This study aimed to assess the diagnostic performance of prostate-specific antigen density in detecting prostate cancer.Materials and methods: A retrospective analysis of histologically proven benign and malignant prostate diseases, submitted in the histopathology department was performed from April 2019 to March 2020. The diagnostic performance of prostate-specific antigen density was assessed and its optimum cut-off value was determined using the receiver operating characteristic curves. The diagnostic efficacy of prostate-specific antigen density was also compared with prostate-specific antigen in detecting prostate cancer.Results: The AUC to predict prostate cancer was 0.89 (95% CI 0.79-0.98. p